Tackling inflation in Nigeria: Monetary or fiscal policy? An empirical assessment of the effectiveness of the simultaneous implementation of the policies (Global Business Management Review (GBMR), 2020)
The study is aimed at empirically assessing between monetary policy and fiscal policy, the most effective in combating and tackling inflation in Nigeria, especially when implemented simultaneously – the effect of the concurrent implementation of the two policies on inflation. The variables of the policies are based on market information, money market equilibrium (LM Curve) for monetary policy, and product market equilibrium (IS Curve) for fiscal policy. The research makes use of the Autoregressive Distributed Lag Model (ARDL). Data for Nigerian was used from 1970 – 2016. The findings show that monetary and fiscal policies can be implemented concurrently as monetary policy is the best for a short-run solution during the fiscal policy for a long-run solution. The findings of the study are based on Nigerian data utilized for the period 1970 – 2016 and the method of data analysis adopted – ARDL, as well as variables selection based on the general equilibrium of money and product market. The findings of the study clearly show that monetary and fiscal policies can be used simultaneously to tackle inflation in Nigeria successfully, being effective in combating inflation in different periods (short-run or long-run). The study attempted to harmonize the incompatible theories and their policies to see whether the policies can be utilized concurrently since the policies are aimed at effecting price stability. The research’s findings confirm the feasibility of implementing the two policies concurrently and their effects to be felt or realized in different periods – short-runs and long-runs.